Intrinsically-safe transformers primarily for bell-signalling circuits - British Standards Institution (London BSI, 1956)
Acoustic signals, Bells, Electrically-operated devices, Circuits, Transformers, Single-phase transformers, Electric enclosures, Electric terminals, Cable junctions, Short-circuit currents, Temperature rise, High-voltage tests, Short-circuit current tests, Marking, Inductance measurement, Type i protected electrical equipment, Mining equipment
Withdrawn
Cross References BS 171, BS 229, BS 355, BS 542, BS 601, BS 1259, BS 1975
Keywords: Transformers -- Standards